2005
DOI: 10.1038/nature03298
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the H-cluster framework of iron-only hydrogenase

Abstract: The metal-sulphur active sites of hydrogenases catalyse hydrogen evolution or uptake at rapid rates. Understanding the structure and function of these active sites--through mechanistic studies of hydrogenases, synthetic assemblies and in silico models--will help guide the design of new materials for hydrogen production or uptake. Here we report the assembly of the iron-sulphur framework of the active site of iron-only hydrogenase (the H-cluster), and show that it functions as an electrocatalyst for proton redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
412
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(427 citation statements)
references
References 28 publications
8
412
0
5
Order By: Relevance
“…Examples of molybdenum-and iron-based catalysts have also been reported. [14][15][16] Significant advances have been realized with iron-thiolate complexes of the type [Fe 2 (m-SRS)(CO) 6Àx L x ] (R= organic group, L = electron-donor ligand, x 4), [17][18][19][20][21][22][23][24][25] which are simplified models of the Fe 2 S 2 subunit of iron-iron hydrogenase enzymes. [26] The utilization of these iron-thiolate complexes for visible light-driven H 2 production has been recently reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of molybdenum-and iron-based catalysts have also been reported. [14][15][16] Significant advances have been realized with iron-thiolate complexes of the type [Fe 2 (m-SRS)(CO) 6Àx L x ] (R= organic group, L = electron-donor ligand, x 4), [17][18][19][20][21][22][23][24][25] which are simplified models of the Fe 2 S 2 subunit of iron-iron hydrogenase enzymes. [26] The utilization of these iron-thiolate complexes for visible light-driven H 2 production has been recently reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…As the +Fe-N-O of the free (bmedach)Fe(NO) metallodithiolate ligand is 148(2)°, this metric suggests that the electron density drained from the Fe(NO) unit via the bridging thiolates in 1 red is less than that in 1 þ ; that is, the nitrosyls act in concert to accommodate the redox level that is largely changing within the Fe(NO) 2 unit. Attempts to further reduce 1 red using stronger reductants such as KC 8 or Na þ (benzophenone À ) resulted in decomposition and rearrangement with the only identifiable product being reduced Roussin's red ester (see Supplementary Methods for details) 18 .…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Biochemical studies have shown that the redox active 4Fe4S cluster that is directly attached to the 2Fe subsite is required for the extraordinary activity of the enzyme. However, intricate molecular constructions with exogeneous redox active centres attached to the diiron unit that mimic the structure of the full H-cluster suffer from instability and low activity 8 . Full catalytic activity for proton reduction approaching the efficiency of the enzyme has only been achieved in hybrid constructs where the synthetic model (m-(SCH 2 ) 2 NH)[Fe(CO) 2 (CN)] 2 2 À has been inserted into the apo-[FeFe]-H 2 ase protein 9,10 .…”
mentioning
confidence: 99%
“…Platinum is very efficient in catalyzing H 2 production, but the low natural abundance and high cost of this noble metal restrict its widespread utilization 9, 10. Progress has been made in identifying HER catalysts by the use of molecular complexes consisting of earth‐abundant metals, such as Fe,11, 12, 13, 14, 15 Co,9, 16, 17, 18, 19, 20 Ni,21, 22, 23, 24, 25 and Mo 26, 27. For example, Co and Fe complexes of N‐based macrocyclic ligands (e.g.…”
mentioning
confidence: 99%